Investigation of Stellantchasmus falcatus metacercariae in half-beaked fish, Dermogenus pusillus from four districts of Chiang Mai Province, Thailand - Sripalwit P. (2014)
Half-beaked fish, Dermogenus pusillus, collected from Mueang, Hang Dong, Doi Saket and Saraphi Districts, Chiang Mai Province, were examined for their infection status with Stellantchasmus falcatus (Digenea: Heterophyidae) metacercariae. The infection rate of the fish was 100%. Fish in three of four districts were found only to have metacercariae of S. falcatus, whereas those in Saraphi District had mixed infections with metacercariae of Posthodiplostomum sp. The intensity of S. falcatus infection per fish varied; 652-1,342 (mean 999.5), 562-2,422 (1,323.1), 185-2,492 (502.6), and 22-550 (210.4) in Mueang, Hang Dong, Saraphi, and Doi Saket Districts, respectively. The body portions of the fish with the heaviest metacercarial infection were the muscles, in all districts. The present study confirms that half-beaked fish in Chiang Mai Province are heavily infected with S. falcatus metacercariae.